The analysis of gait patterns using a color camera and computer vision - Batysheva, T. T.; Tikhonov, S. V.; Alekseeva, M. V.; Peganskiy, D. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to validate the approach for determining human walking metrics through the application of neural networks and computer vision techniques.